Markers of Glycemic Control and Neonatal Morbidity in High-Risk Insulin-Resistant Pregnancies - Cahill, Alison G.; Tuuli, Methodius G.; Colvin, Ryan; Cade, W. Todd; Macones, George A. (American Journal of Perinatology, 2016)
Objective This study aims to determine whether fructosamine, glycated hemoglobin A1C (HbA1c), or mean fasting glucose levels associate with birth outcomes in diabetic women.Study Design A prospective cohort study of women with singleton, nonanomalous pregnancies and diagnosis of diabetes (gestational or pregestational). Daily average self-measured fasting serum glucose levels were collected, as well as HbA1c and fructosamine levels at delivery. The primary outcome was neonatal composite morbidity, defined as having one or more of the following: respiratory distress syndrome, hyperbilirubinemia, perinatal death, shoulder dystocia, and hypoglycemia requiring treatment. Secondary outcomes included macrosomia (≥ 4,000 g).Results Among neonates delivered by 301 study-eligible women (97 with gestational and 204 with pregestational diabetes), incidences of composite morbidity (n = 147, 48.8%) and macrosomia (n = 49, 16.3%) were high. Macrosomia occurred more frequently in infants of pregestational than gestational diabetic mothers (22.7 vs. 13.2%, p = 0.04), composite morbidities were not significantly different (52.2 vs. 42.3%, p = 0.14). HbA1c > 8.0 significantly increased risk of morbidity and macrosomia (relative risk, 4.29; 95% confidence interval, 1.62–11.3).Conclusions Late third-trimester HbA1c, but not fructosamine or mean blood glucose levels, was associated with increased morbidity in infants of diabetic mothers. Third-trimester HbA1c could be clinically useful for counseling regarding neonatal risks in women with diabetes.
Keywords: pregnancy; insulin resistance; glucose; neonatal outcomes